Effects of Cinacalcet on Atherosclerotic and Nonatherosclerotic Cardiovascular Events in Patients Receiving Hemodialysis: The EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular Events (EVOLVE) Trial. Issue 6 (17th November 2014) - Wheeler, David C.; London, Gerard M.; Parfrey, Patrick S.; Block, Geoffrey A.; Correa‐Rotter, Ricardo; Dehmel, Bastian; Drüeke, Tilman B.; Floege, Jürgen; Kubo, Yumi; Mahaffey, Kenneth W.; Goodman, William G.; Moe, Sharon M.; et al.
Abstract : Background: Premature cardiovascular disease limits the duration and quality of life on long‐term hemodialysis. The objective of this study was to define the frequency of fatal and nonfatal cardiovascular events attributable to atherosclerotic and nonatherosclerotic mechanisms, risk factors for these events, and the effects of cinacalcet, using adjudicated data collected during the EValuation of Cinacalcet HCl Therapy to Lower CardioVascular Events (EVOLVE) Trial. Methods and Results: EVOLVE was a randomized, double‐blind, placebo‐controlled clinical trial that randomized 3883 hemodialysis patients with moderate to severe secondary hyperparathyroidism to cinacalcet or matched placebo for up to 64 months. For this post hoc analysis, the outcome measure was fatal and nonfatal cardiovascular events reflecting atherosclerotic and nonatherosclerotic cardiovascular diseases. During the trial, 1518 patients experienced an adjudicated cardiovascular event, including 958 attributable to nonatherosclerotic disease. Of 1421 deaths during the trial, 768 (54%) were due to cardiovascular disease. Sudden death was the most frequent fatal cardiovascular event, accounting for 24.5% of overall mortality. Combining fatal and nonfatal cardiovascular events, randomization to cinacalcet reduced the rates of sudden death and heart failure. Patients randomized to cinacalcet experienced fewer nonatherosclerotic cardiovascular events (adjusted relative hazard 0.84, 95% CI 0.74 to 0.96), while the effect of cinacalcet on atherosclerotic events did not reach statistical significance. Conclusions: Accepting the limitations of post hoc analysis, any benefits of cinacalcet on cardiovascular disease in the context of hemodialysis may result from attenuation of nonatherosclerotic processes. Clinical Trials Registration: Unique identifier: NCT00345839. URL:ClinicalTrials.gov .